Disparity in Availability of Public “General” Secondary Teachers in The City of Dschang And Its Periphery - TAFELEFACK, Jolin; NANA, Claudin Karim; KUÉTÉ , Martin (CenRaPS Journal of Social Sciences, 2020)
To effectively meet the demand for education, the Cameroon is called upon to trained teachers and ensure their equitable distribution throughout the country. However, in Menoua Division, the situation is different as compared to the rest of the country. The spatial distribution of teachers per school shows unequal distribution between the town and its periphery. Indeed, while the number of pupils in general secondary schools is increasing. This increase is not accompanied by an increase in the number of teachers. This general shortage does not present itself within the city as compared to its periphery. The principal objective of this reflection is to show the reasons accounting for these disparities. The methodology applies include both qualitative and quantitative data from teachers and administrative officials of general secondary education. The reflection leads to three main results. Firstly, the shortage of teachers couple with the mechanism for assigning teachers favor’s schools in urban area of Dschang to the detriment of its periphery. Secondly, is that secondary school teachers use the loopholes in the teacher assignment to position themselves in urban schools where they avoid the periphery which they stigmatize. Finally, this disparity has many consequences in the demand of education.